Sebaran Dan Ketersediaan Sarana Prasarana Air di Kota Tangerang Selatan - Rachmawati, Nia (Fakultas Teknik, Universitas Brawijaya, 2012)
The expansion and development requires infrastructures in order to serve and support the activities in various sectors between regions. Integrated infrastructure system serves as the wheels of activities to spread and serve the needs of the region. The successful of regional development could be visible from the spreading infrastructure to serves region needs. The South Tangerang City as the new city should pay attention to the expansion basic needs of water as a basic infrastructure. Identification of spreading water could be visible from the amount of infrastructure require needs. The purpose of this study are to identify spread of the water infrastructure, to evaluate the availability of the water infrastructure, to analyze the access to the water infrastructure. The methods of this study is using the digitization of the water supply in South Tangerang City, calculating the spread and availability of water infrastructure based on population and spatial analyzing to access point and service areas. The results of the analysis show the spreading and the availability of water infrastructure in services area of South Tangerang City: the spreading of water infrastructure only in two region, the availability of water infrastructure in The South Tangerang has not meet the region.Keywords: Spreading, Availability, Water Infrastructure.